Sensitivity to colicin Js, one of important characteristics of Escherichia coli strains belonging to enteroinvasive serovars - Horák, V; Sobotková, J (Zentralblatt fur Bakteriologie, Mikrobiologie, und Hygiene. Series A, Medical microbiology, infectious diseases, virology, parasitology, 1988)
Of the 96 E. coli strains belonging to 9 enteroinvasive serovars 79 (82.3%) turned out to be sensitive to colicin Js but none of the 115 strains of E. coli isolates from the feces of healthy persons without diarrhoea exhibited this type of sensitivity reaction. Of the colicin Js-sensitive strains, 89.9% (71 out of 79) gave also positive reactions in the Serény test for enteroinvasiveness. The remaining strains belonging to enterointervasive E. coli serovars but showing no sensitivity to colicin Js were as a rule negative in the Serény test.
Keywords: morčata; průjem; Animals; Guinea Pigs; lidé; Escherichia coli Infections; infekce vyvolané Escherichia coli; zvířata; feces; Feces; Escherichia coli; Colicins; Diarrhea; koliciny; Humans